Prevalence, clinical characteristics, and 3-dimensional radiographic analysis of supernumerary teeth in Guangzhou, China: a retrospective study - Lidan He; Guoying Que; Xiaoxia Yang; Siqi Yan; Song Luo (BMC, 2023)
Abstract Objective The aim was to investigate the prevalence and clinical and 3-dimensional (3D) radiographic characteristics of supernumerary teeth (ST) in a paediatric dental population. The factors associated with ST eruption potential were analysed, and the optimal extraction time for nonerupted ST was discussed. Methods A retrospective study was performed in a 13,336-participant baseline population aged 3-12 years for whom panoramic radiographs had been obtained in the hospital from 2019 to 2021. The medical records and radiographic data were reviewed to identify patients with ST. Both the demographic variables and ST characteristics were recorded and analysed . Results In total, 890 patients with 1,180 ST were screened from the 13,336 baseline population. The ratio of males (679) to females (211) was approximately 3.2:1. Generally, ST occurred singularly and were frequently found in the maxilla (98.1%). A total of 40.8% of ST were erupted, and the 6-year-old age group presented the highest eruption rate (57.8%). The eruption rate of ST was highly negatively correlated with age. A total of 598 patients additionally underwent cone- beam computed tomography (CBCT). According to the CBCT images, the majority of ST were conical, normally oriented, palatally situated, nonerupted and symptomatic. The most common ST-associated complication was failed eruption of adjacent teeth. In addition, symptomatic ST were more common in the 7- to 8- and 9- to 10-year-old age groups. The eruption rate of ST was 25.3% among the patients who had undergone CBCT. A normal orientation and the labial position were significant protective factors for ST eruption, with odds ratios (ORs) of 0.004 (0.000-0.046) and 0.086 (0.007-1.002), respectively. Age and the palatal position were significant risk factors, with ORs of 1.193 (1.065-1.337) and 2.352 (1.377-4.02), respectively. Conclusions This study provides a detailed analysis of ST characteristics in 3-12 year old children. Age as well as the position and orientation of ST were reliable predictors of the ST eruption. An age of 6 years old may be the optimal time for extraction of nonerupted ST to maximize the utilization of eruption potential and reduce the incidence of ST-associated complications.